Gone, but not forgotten - Margolin, Phillip (New York : Bantam Books, 1994)
Investigators look into the disappearance of the wives of several prominent businessmen in Portland, Oregon which occur ten years after an identical series of disappearances in Hunter's Point, New York.
National College of Business and Arts
Keywords: Women lawyers -- Fiction; Detective and mystery fiction